Experimental and numerical analysis of an electrical submersible pump's performance handling non-newtonian complex flows (2019)
This work aims to carry out an exhaustive analysis of the performance and internal flow features of a multistage ESP when handling complex non-Newtonian flows. The first stage of this work focuses on the comparative analysis of single-phase Newtonian and non-Newtonian fluids. The second part jointly analyzes the performance and flow behavior of the ESP when handling two-phase oil-water flow and unstable emulsions. A novel coupled CFD-PBM approach was implemented to provide a more robust modelling of the emulsions formed. The testing facility consisted of a four-stage ESP located in a closed-loop arrangement in which the flowrate was manipulated and the pressure rise and power consumption by the ESP's motor was monitored. The CFD head rise results in all cases were in excellent agreement with the experimental data gathered, with MSE < =10%. The computed efficiencies were also in good agreement, with slightly higher deviations (~15%) and an overpredictive tendency. The only exception was observed for the PBM simulations, specifically the concentrated O/W emulsion case. This was attributed to the lack of a rheology closure model for such system. It was consistently noticed that a shear-thinning non-Newtonian behavior consisting of a strong viscosity drop and a low range of effective viscosities dramatically improved the ESPs performance. Flow systems with such properties will promote a lower brake power consumption, a higher head rise (in average) and a displacement of the BEP towards higher flowrates. The internal flow behavior was mostly governed by effective viscosity variations and the flowrate of operation. At lower flowrates and high viscosity variability, the formation of recirculation zones and backflow currents were detected. At higher flowrates near the BEP, these structures disappeared, promoting a well-oriented flow through the impellers and diffusers, regardless of the flow system handled.